An optimal and flexible control strategy for active filtering and power factor correction under non-sinusoidal line voltages. - Rafiei, S.M.-R.
This paper gives a new insight into the concept of load compensation under distorted voltages. Achieving both unity power factor (UPF) and perfect compensation of current harmonics are not possible where competition will arise between these two important factors. Through evaluating the present control strategies, a generalized, optimal, and flexible control strategy (OFC) for harmonic compensation of utility lines is proposed. The proposed control strategy, which provides a unified and highly flexible compensation framework has the ability of programming for perfect current harmonics compensation, or (UPF) accomplishment, or other newly defined objectives such as maximizing the power-factor subject to some adjustable constraints on the level of current harmonics and unbalancing via an on-line optimization algorithm. The strategy can fulfill the IEEE-519 standards requirements, while guaranteeing the best achievable power factor and optimum required rating for the compensator. Theoretical concepts and practical features of the proposed control strategy have been shown through extensive simulation studies using MATLAB/SIMULINK programs
Keywords: IEEE-519 standards; MATLAB/SIMULINK programs; Active filtering; Computer simulation; Control design; Control simulation; Current harmonics; Distorted voltages; Harmonic compensation; Load compensation; Nonsinusoidal line voltages; Optimal flexible control strategy; Power factor correction